Leptin as Clinical Target - Cai, Chunlin; Shi, Fu-Dong; Matarese, Giuseppe; Cava, Antonio L. (Recent Patents on Inflammation & Allergy Drug Discovery, 2009)
Leptin is an adipocyte-derived hormone with pleiotropic effects on energy homeostasis, endocrine and reproductive functions, and immune responses. The multiple actions of leptin have led to the design and development of several leptin-based approaches to modulate the metabolic and endocrine status, to reduce inflammation, and to improve immune responses. Here, we review the current patents on leptin in different clinic applications.
Keywords: therapeutics